2013
DOI: 10.5267/j.msl.2013.08.022
|View full text |Cite
|
Sign up to set email alerts
|

A study on effects of knowledge management on the success of customer relationship management

Abstract: Nowadays, it is widely accepted that knowledge is the primary source of adding more value to organizations and business units. Customer relationship management (CRM), on the other hand is the main bridge for building a connection between management team and users and a good CRM also contributes to firms in terms of customer retention and getting more market share through word of mouth advertisement. In this paper, we present an empirical investigation to find the effect of knowledge on CRM in one of Iranian ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This connotes that the CRM concept assists SMEs in retain existing customers, attract new customers, build customer confidence, and inform customers about an array of products and services with aim of increasing profits or prevent losses. To support this assertion, Hassan and Parvez [14] postulated that CRM is a powerful marketing tool to communicate with and retain existing customers. Similarly, Garrido-Moreno and Padilla-Melendez [15] also confirmed that CRM assists companies to find it more profitable to retain existing customers rather than attract new ones.…”
Section: Literature Review 21 Customer Relationship Management (Crm)mentioning
confidence: 99%
See 1 more Smart Citation
“…This connotes that the CRM concept assists SMEs in retain existing customers, attract new customers, build customer confidence, and inform customers about an array of products and services with aim of increasing profits or prevent losses. To support this assertion, Hassan and Parvez [14] postulated that CRM is a powerful marketing tool to communicate with and retain existing customers. Similarly, Garrido-Moreno and Padilla-Melendez [15] also confirmed that CRM assists companies to find it more profitable to retain existing customers rather than attract new ones.…”
Section: Literature Review 21 Customer Relationship Management (Crm)mentioning
confidence: 99%
“…A plethora of studies on CRM has been carried out by academic scholars from diverse fields of study in both advanced economies and developing economies [7,8,9,10,11,12,13,14]. However, most of the studies focused on large organizations while small size organizations have not been explored especially in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of management and organization in their survey, waiting time to receive services was the most important factor followed by geographic location of the hospital, peaceful and quiet environment and quality of services. Hassani et al (2013) performed an investigation on the effects of knowledge management on the success of customer relationship management and reported that knowledge impacted CRM positively in terms of customer satisfaction, customer loyalty and trust. Ryals and Knox (2001) investigated the cross-functional issues in the implementation of relationship marketing through customer relationship management.…”
Section: Introductionmentioning
confidence: 99%